Data visualization on Smart Card Attendance System / Nursyahidah Nasharuddin - Nasharuddin, Nursyahidah (2012)
A smart card can be defined as a plastic card with implanted microprocessor chip usually like small gold-colored metal that be able to store, process, calculate, manage, and encrypt large amount of the data in chip which can be either value or information or both of them. There are lot of applications used smart card in different sector for example banking and transportation. In visualization technique, usually graphs and charts are used for reviewing financial, statistical, mathematical, scientific, engineering and other area of application. Lines graphs, bar charts, pie charts, surface graphs, contour plots and other visualize in 2-dimensional, 3- dimensional or higher-dimensional spaces are the examples of data plots.This research is to develop the Data Visualization of Smart Card Attendance System. This system are used IRIS SCR21U as a smart card reader and MyKad(Identity Card) as smart card. The number of student attendance can be calculate and be plot out by using 2-Dimensional bar chart as a data visualization. This research methodology consists of seven stages which are project overview, knowledge acquisition, requirement analysis, system design, system implementation, system testing and documentation. Every stage in methodology are being used for better understanding of the system. The accuracy of this prototype is about 70 percent. The result showed that the accuracy of the system is 70%. In the future, this system will be added the security protection to make the system is safer to use by admin in order to modifying the student attendance in the system.